2018
DOI: 10.3390/ma11061016
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Performance Analysis of Modified Sodium Acetate Trihydrate

Abstract: In order to solve undercooling and phase separation of sodium acetate trihydrate (SAT), experimental screening method was used to select nucleating agents and thickeners that are suitable for SAT, and the optimal ratio was identified. Through screening experiments of nucleating agents, it is found that disodium hydrogen phosphate can be used as an effective nucleating agent for SAT. When the weight content of disodium hydrogen phosphate in SAT is 2%, the degree of undercooling was reduced to approximately 2 K.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Conventionally, synthetic polymers, such as poly (acrylamideco-acrylic acid) partial sodium salt, sodium polyacrylate, and polyvinyl alcohol, have been applied to address the phase separation issue of salt hydrate PCMs. [153][154][155][156] However, the non-sustainability and expensiveness limit their wide applications in energy storage applications. Although carboxyl methyl cellulose (CMC) as a cellulose derivative has been considered as the most prevailing thickening agent for preparing form-stable composite PCM slurries, developing more cost-effective substitutes remains warmly welcomed.…”
Section: Nanocellulose-based Composite Pcm Slurriesmentioning
confidence: 99%
“…Conventionally, synthetic polymers, such as poly (acrylamideco-acrylic acid) partial sodium salt, sodium polyacrylate, and polyvinyl alcohol, have been applied to address the phase separation issue of salt hydrate PCMs. [153][154][155][156] However, the non-sustainability and expensiveness limit their wide applications in energy storage applications. Although carboxyl methyl cellulose (CMC) as a cellulose derivative has been considered as the most prevailing thickening agent for preparing form-stable composite PCM slurries, developing more cost-effective substitutes remains warmly welcomed.…”
Section: Nanocellulose-based Composite Pcm Slurriesmentioning
confidence: 99%
“…Phase separation occurs due to the difference of densities of salt hydrate and water in the melting process, and this can be addressed by adding thickening agents such as polyacrylic amide, poly (acrylamide-co-acrylic acid) partial sodium salt, sodium polyacrylate, and polyvinyl alcohol [15][16][17][18]. These materials are soluble in aqueous phase, and increase the viscosity of salt hydrate solution so that flowing or precipitation of salt hydrate is hindered.…”
Section: Effect Of Cnfs On Phase Stability Of Pcmsmentioning
confidence: 99%
“…[19] Many scholars have conducted many studies on the supercooling of SAT, and the main method for suppressing this supercooling is the addition of hydrated salts or nanonucleating agents. Hua et al [20] added 1.5 wt% xanthan gum and 2 wt% DHPD to SAT and found that for the new composite of SAT/1.5 wt% XG/2 wt% DHPD, the supercooling degree was only 1.5 K, and the latent heat of phase change was 245.3 kJ/ kg. Wang et al [21] showed that the supercooling degree of SAT composited with 2 wt% Na 4 P 2 O 7 ⋅ 10H 2 O and 1.5 wt% polyacrylamide (PAM) was less than 5 °C.…”
Section: Introductionmentioning
confidence: 99%